Mobile banking and mobile payment acceptance - Baptista, Gonçalo da Costa Aleixo Monteiro Melhorado (2017)
A thesis submitted in partial fulfillment of the requirements for the degree of Doctor in Information Management, specialization in Information and Decision Systems